Breastfeeding and infant growth outcomes in the context of intensive peer counselling support in two communities in Bangladesh. Issue 1 (December 2016) - Haider, Rukhsana; Saha, Kuntal
Abstract Background Exclusive breastfeeding and growth faltering during infancy remain challenges in Bangladesh. The Training & Assistance for Health & Nutrition Foundation has been working to address this gap through community-based peer counsellors since 2000. In this paper, we assessed the programme's progress, particularly with respect to early initiation of breastfeeding and exclusive breastfeeding for normal birth weight, as well as for low birth weight (LBW) infants. Methods The peer counselling programme is continuing in rural and urban areas of Bangladesh, but only data collected between January 2013 and June 2015 is presented in this descriptive study. Intensive breastfeeding counselling was provided to women during the third trimester of pregnancy and 6 months postpartum by well-trained peer counsellors. They recorded data on infants' birth weight, feeding practices and body weight every month and submitted these for computer entry. Weight measurements were converted to weight-for-age Z-scores (WAZ) and growth patterns assessed by comparing attained body weights with the World Health Organization (WHO) 2006 Child Growth Standards. Results A total of 994 infants were born during the study period; 94 % were normal birth weight and 6 % were LBW (<2.5 kg). Initiation of breastfeeding within one hour of birth was reported by 94 % of counselled mothers in both groups. The prevalence of exclusive breastfeeding at 6 months was 94 % in the normal birth weight infants and 92 % in the LBW infants, and their mean body weights were 7.5 ± 0.8 kg and 6.6 ± 0.7 kg respectively. There was no growth faltering in these infants during 6 months. Underweight rates in normal birth weight infants remained similar (2.2 % at 1 month and 2.5 % at 6 months), whereas underweight rates in LBW infants decreased from 42.1 % at 1 month to 21.1 % at 6 months. Conclusions In the context of a well-structured programme setting, and under the described circumstances, it seems likely that the well-trained and supervised community-based peer counsellors could assist in encouraging and helping mothers of both normal birth weight and LBW infants to initiate breastfeeding within one hour and to continue exclusive breastfeeding until 6 months of age. Our data suggest that they may also have contributed towards prevention of growth faltering in these infants.